Protein refolding in an oscillatory-flow-mixing reactor - Lee, C. T. (2001)
We demonstrate that an oscillatory flow-mixing reactor (OFMR) operating in fed-batch mode is viable for industrial protein refolding. OFMR offers the advantage of uniform, controllable, and scalable mixing. Denatured lysozyme (15 mg/ml, in 8 M guanidine hydrochloride (GuHCl) or 8 M urea, and 32 mM dithiothreitol) was fed into a 150-ml OFMR for 2 h and the final solution was incubated for a further 3 h. A control experiment used a small perfectly-mixed stirred-tank reactor (STR). Both systems were operated under mild and intense mixing conditions. With GuHCl denaturation, the refolding yield profiles throughout the 5 h period were identical in both the OFMR and STR, and yield was independent of mixing intensity. Conversely, refolding yield in both reactors following urea denaturation decreased from 25% to 15% as mixing intensity decreased. Clearly, imperfect mixing in large STRs may lead to reduced refolding yield when urea is used as a denaturant. This effect can be minimised by using a reactor with uniform, controllable and scaleable mixing, such as the OFMR.